2018 European Conference on Optical Communication (ECOC) 2018
DOI: 10.1109/ecoc.2018.8535497
|View full text |Cite
|
Sign up to set email alerts
|

Field-Trial of Machine Learning-Assisted Quantum Key Distribution (QKD) Networking with SDN

Abstract: We demonstrated, for the first time, a machine-learning method to assist the coexistence between quantum and classical communication channels. Software-defined networking was used to successfully enable the key generation and transmission over a city and campus network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Other examples of how the SDN and network function virtualization (NFV) paradigms-widely adopted in classical networks-can be extended to quantum networks, including internet of Things (IoT) [54] and 5G [55] applications, are reported in [55][56][57][58][59][60][61][62][63], further proving the importance of moving from current point-to-point setups to more complex topologies. Furthermore, recent advances in machine learning (ML) can greatly help to improve the automation of QKD systems, whose performance depends of many parameters that must be finely tuned, thereby significantly decreasing operational and maintenance costs.…”
Section: Qkd Networkingmentioning
confidence: 99%
“…Other examples of how the SDN and network function virtualization (NFV) paradigms-widely adopted in classical networks-can be extended to quantum networks, including internet of Things (IoT) [54] and 5G [55] applications, are reported in [55][56][57][58][59][60][61][62][63], further proving the importance of moving from current point-to-point setups to more complex topologies. Furthermore, recent advances in machine learning (ML) can greatly help to improve the automation of QKD systems, whose performance depends of many parameters that must be finely tuned, thereby significantly decreasing operational and maintenance costs.…”
Section: Qkd Networkingmentioning
confidence: 99%
“…In recent years, the desire to reduce the capital expenditures of QKD network deployment has motivated the research of QKD integration with classical networks, where both of physical-layer performance and network-layer performance are taken into account. In order to improve the physical-layer performance such as secret-key rate and achievable distance, a number of analytical studies [30], [43], system experiments [31], [34], [36], and field trials [33], [44] have been carried out. On the other hand, several resource assignment strategies have been proposed to optimize the network-layer performance such as blocking probability and resource utilization when QKD coexists with the classical networks [32], [35].…”
Section: A Qkd Network Deploymentmentioning
confidence: 99%
“…In [50], the end-to-end key on demand service provisioning over a SDN-controlled QKD network was demonstrated. In [44], SDN was combined with machine learning to achieve dynamic and optimal wavelength allocation for both quantum and classical channels. Meanwhile, with regards to QKP technique, several QKPs were constructed to enable on-demand secret-key volume allocation for control channels and data channels in a software defined optical network [40].…”
Section: B Qkd Network Managementmentioning
confidence: 99%
“…In 2017, Chistyakov et al used a subcarrier quantum system to propose a dynamic quantum routing and secure communication method based on OpenFlow protocol in SDN, further demonstrating the feasibility of applying SDN techniques to QKD networks [22]. In 2018, to effectively alleviate the problem of in-band noise in the QKD network, Ou et al used machine learning-based approach to estimate physical performances of quantum channel for the successful key generation and transmission [23]. In the same year, Hugues-Salas et al demonstrated that QKD resources can be successfully allocated through SDN control under DDoS attacks [24].…”
Section: Experimental Verification Of the Networkmentioning
confidence: 99%